Fostering learning ownership and environmental literacy: Problem-based learning with a humanistic Merdeka Belajar approach - Alma Dwi Rahmawati; Dwi Listyorini; Indra Fardhani (University of Muhammadiyah Malang, 2026)
Background: The elimination of national exams and the implementation of automatic grade promotion in the Kurikulum Merdeka have contributed to a decline in student ownership of their learning, exacerbated by the low levels of environmental literacy observed in schools. Problem-based learning (PBL) integrated with the Humanistik-Merdeka Belajar (HMB) approach has the potential to improve environmental literacy and ownership of learning. Objectives: This study aimed to determine the effect of PBL-HMB on learning ownership and environmental literacy in high school students. Methods: This quasi-experimental non-equivalent pre-test-post-test control group study involved three groups: the experimental group (PBL-HMB), the positive control group (PBL), and the negative control group (Conventional model). Multiple-choice test instruments and questionnaires were used as data collection instruments. The data obtained were analyzed using One-Way ANCOVA. Results: This study found that PBL-HMB had a significant influence on both dependent variables. Conclusion: The HMB approach in the PBL model was proven to increase learning ownership and environmental literacy.